PENINGKATAN KETERAMPILAN MEMBACA BERORIENTASI STRATEGI TPRC (THINK, PREDICT, READ, CONNECT) DI KELAS VI SEKOLAH DASAR NEGERI 023 PULAU KIJANG KECAMATAN RETEH - Rahmawati Rahmawati (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Learning to read in primary school is divided into two, namely beginning reading and reading comprehension. This reading skill needs to be applied when the child is still as early as possible because reading is the main basis for students. But there are some obstacles in reading skills, such as lack of reference to the stages of reading, lack of teacher guidance to summarize the contents of the reading, and lack of enthusiasm of students in learning to read. This research is a classroom action research which consists of two cycles. Each cycle consists of action planning, action, observation and reflection. The subject of this research was students of class VI of the State primery school 023 Kijang Island, Reteh District, which amounted to 11 people. This study aims to improve students' reading skills which are rooted in the strategy of think, predict, read, connect (TPRC). The results of this study indicate, the initial data of students on reading skills amounted to 59.7 in the medium category, in the first cycle, the average value of students' reading skills increased to 76.03 in the high category. while in cycle II, the average value of students' reading skills again increased to 88.9 in very high categories. The increase in the average value seen from the basic score to the second cycle is 29.2 points. These results prove that the application of the TPRC strategy can improve reading skills of students in class VI 023 public primary school kijang island, reteh district.